(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Initial assessment of the effectiveness of knowledge and attitude change after applying the AIDET standard communication model at Quan Son District General Hospital, Thanh Hoa Province in 2024. Subject and method: Intervention study, comparing and evaluating before and after intervention. The subjects are healthcare workers at Quan Son District General Hospital, Thanh Hoa Province (1/2024 - 11/2024). Results: After the training, healthcare workers had a high level of knowledge, attitude and intention to apply the AIDET model, specifically: The rate of knowledge reaching the AIDET criteria before the training was 47.7%, increasing to 84.6% after the training (p<0.05). The rate of intention to use the model was 64.6%. If the Hospital implemented the AIDET model, healthcare workers showed a willingness to participate of 76.9%. Conclusion: the initial application of the AIDET communication model at Quan Son District General Hospital, Thanh Hoa province has been effective in changing and improving the knowledge, attitudes and intentions of healthcare workers to apply this model.